Comparative analysis of titanium clip prostheses for partial ossiculoplasty - Mantsopoulos, Konstantinos; Thimsen, Vivian; Taha, Lava; Eisenhut, Felix; Müller-Hübner, Sarina Katrin Ursel; Sievert, Matti; Iro, Heinrich; Hornung, Joachim (American Journal of Otolaryngology, 2021)
Objectives: The aim of our study was to perform a comparative analysis in our cases with titanium partial clip ossiculoplasty in terms of audiometric outcome and extrusion rates as well as to review the literature for relevant information on this surgical issue. Materials and methods: The records of all patients who had undergone primary partial ossiculoplasty with the implantation of a CliP® Partial Prosthesis Dresden Type (CPPDT, group A) or a CliP Partial FlexiBAL® (CPF, Group B, both Heinz Kurz GmbH, Dusslingen, Germany) between 2012 and 2020 were studied retrospectively. Results: 274 patients made up our study sample (148 men, 126 women, male to female ratio: 1.17). Their mean age at the time of first surgery was 39.6 years (range: 4–79 years). The mean preoperative air-bone gap (ABG) was 22.7dΒ ± 10.5 dB. Mean follow-up was approximately 4 months (1–12 months). The mean postoperative ABG was 15.7 ± 8.1 dB. In total, the postoperative ABG was significantly improved compared to preoperative values (P < 0.001). Surgical success, defined as an ABG ≤ 20 dB, was achieved in the majority of our study patients (210/274, 76.6%). Extrusion of the prosthesis was detected in 3/216 CPF and 5/58 CPPDT cases (p = 0.012). Comparison of both prosthesis groups revealed a significantly better audiological outcome for the patients with ossicular reconstruction using CPF. A significantly better audiological outcome was detected in the cases with a normal aeration of the middle ear. Discussion: Titanium clip partial ossiculoplasty is a reliable component of modern tympanoplasty, allowing a satisfying audiologic outcome. The higher adaptability of the CPF to the changing postoperative circumstances and the frequently defective aeration of the middle ear is reflected in the better audiologic outcome for this prosthesis.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Air-bone gap; Middle ear; Ossiculoplasty; Outcome; Partial prosthesis; PORP